Cover Crop Management in a Chardonnay/99 Richter Vineyard in the Coastal Wine Grape Region, South Africa. 1. Effect of Two Management Practices on Selected Grass and Broadleaf Species - Fourie, J.C.; Louw, P.J.E.; Agenbag, G.A. (South African Journal of Enology and Viticulture, 2017)
The trial was conducted over a period of 10 years (1993/94 to 2002/03) on a medium textured soil in a Chardonnay/99 Richter vineyard near Stellenbosch (33°55’S, 18°52’E), situated in the Coastal Wine Grape Region of the Western Cape. Sixteen treatments, consisting of three grain species and five N-fixing broadleaf species managed according to two cover crop management practices, were included. These treatments were compared to a control treatment, in which no cover crop was sown and the weeds were controlled mechanically in the work row and chemically in the vine row from the first week of September to the end of March (grapevine growing season). A treatment in which no cover crop was sown and full surface post-emergence chemical control was applied during the grapevine growing season was also included. The different weed control actions were carried out during the first week of September and/or at the end of November, as well as mid October (1999/00 to 2002/03). Secale cereale L. v. Henog (rye), Avena sativa L. v. Overberg (‘Overberg’ oats), Avena strigosa L. v. Saia (‘Saia’ oats) and Vicia faba L. v. Fiord [only if sown annually and controlled chemically before bud break (BB)], showed the ability to produce, on average, significantly more dry matter during winter than the weeds in the region. The dry matter production of all the cover crops increased from the end of August to the end of November if left to complete their life cycles, with the exception of rye and ‘Overberg’ oats sown in early April. None of the cover crop species were able to reestablish successfully. Continuous effective suppression of winter growing weeds (less than 20% of the weed stand in the control) was achieved with ‘Overberg’ oats (BB) and ‘Saia’ oats (BB), while total suppression was achieved for six and five of the 10 years, respectively. Effective, long-term control of the summer growing weeds was obtained with rye (BB), ‘Overberg’ oats (BB) and ‘Saia’ oats (BB).